Pengembangan tes keterampilan pukulan jarak jauh woodball untuk siswa sekolah dasar - Indah Sari Dewi; Danang Pujo Broto (Jurnal Pendidikan Jasmani Indonesia, 2019)
Penelitian ini di latarbelakangi oleh belum adanya tes dan norma tes yang dapat digunakan untuk mengukur keterampilan pukulan jarak jauh woodball untuk siswa sekolah dasar kelas atas yang berusia 10-12 tahun. Tujuan penelitian ini adalah untuk mengkur tingkat kemampuan pukulan jarak jauh woodball siswa sekolah dasar kelas atas yang berusia 10-12 tahun.Penelitian ini menggunakan metode research and development. Sampel uji coba penelitian yang digunakan adalah siswa sekolah dasar kelas atas yang berusia 10-12 tahun yang telah mengikuti ekstrakulikuler woodball di SD Negeri Condongcatur Depok Sleman. Instrumen yang digunakan adalah tes keterampilan pukulan jarak jauh siswa sekolah dasar. Norma penilaian untuk penjumlahan skor 3 lapangan didapat hasil kategori putri skor kurang dari 20 pukulan  termasuk ke dalam kategori sangat baik, 21-25 pukulan termasuk kategori baik, 26-30 termasuk dalam kategori cukup, 31-34 termasuk dalam kategori kurang dan lebih dari 35 pukulan termasuk kategori sangat kurang. Sedangkan untuk kategori putra skor kurang dari 19 pukulan  termasuk ke dalam kategori sangat baik, 20-24 pukulan termasuk kategori baik, 25-29 termasuk dalam kategori cukup, 30-33 termasuk dalam kategori kurang dan lebih dari 34 pukulan termasuk kategori sangat kurang. Woodball long drive skill test development for upper-grade students of elementary school AbstractThis research was based on the consideration of the absence of the tests and norms of test that can be used to measure woodball long drive skills for upper-grade elementary school students in the age of 10-12 years. The aim of this study was to measure the level of woodball long drive ability of upper-grade elementary school students in the age of 10-12 years. This research used research and development methods. The research trial sample were the upper-grade students of elementary school in the age of 10-12 years who have participated in woodball extracurricular activities at SD Negeri Condongcatur Depok Sleman. This research used a long drive skills elementary school students test as the instrument. The norm can be seen from the sum of the scores of 3 fireway. The score of women's category was less than 20 blows that was categorised as very good, 21-25 blows was included in good category, 26-30 was included in the sufficient category, 31-34 was classified in less category and more than 35 blows was classified in very poor category. Whereas for the men's category, the score of less than 19 blows was included in very good category, 20-24 blows classified in good category, 25-29 were in sufficient category, 30-33 was included in less category and more than 34 blows were very less category.